ما وراء ثنائية الصواب والخطأ النحوي: إعادة بناء البيداغوجيا النيوليبرالية في تعليم اللغة العربية عبر التكامل بين نظرية الذكاءات المتعددة، وملكة ابن خلدون، ونظرية النظم للجرجاني - Habib Luthfi; Safira Budiaty Nafi'a; Muhammad Ikhlasul Amal; Bima Riansyah; Dewi Chamidah (Al-Fakkaar, 2026)
Contemporary Arabic Language Teaching (ALT) is critically paralyzed by a neoliberal pedagogical paradigm characterized by market-driven performativity, rigid standardization, and a restrictive "halal-haram" grammatical prescriptivism. This study deconstructs this reductionist framework by synthesizing three distinct theoretical pillars: Howard Gardner’s Multiple Intelligences (MI), Ibn Khaldun’s concept of linguistic malakah (organic competence), and Abd al-Qahir al-Jurjani’s Nazm (theory of syntactic-semantic integration). Employing a philosophical-pedagogical approach through a critical literature review, the study reveals that this theoretical synthesis constructs a transformative epistemology that transcends mere grammatical compliance. First, Gardner’s MI dismantles the cognitive homogenization inherent in standardized language assessments. Second, Ibn Khaldun’s malakah shifts the instructional focus from syntactic accumulation (ṣinā‘ah) to the cultivation of an intuitive linguistic habitus. Third, Al-Jurjani’s Nazm contextualizes grammatical correctness, demonstrating that syntax is inherently meaningless devoid of its structural, semantic, and functional dynamics. Ultimately, this study contributes an emancipatory pedagogical framework that liberates ALT from the trap of commodification and structural reductionism, restoring the language to its dynamic, humanistic, and communicative essence.